Tracking major endocrine disruptors in coastal waters using an integrative approach coupling field-based study and hydrodynamic modeling. (February 2018) - Xu, Elvis Genbo; Chan, S.N.; Choi, K.W.; Lee, Joseph H.W.; Leung, Kenneth M.Y.
Abstract: Many of the world's large coastal cities discharge partially treated wastewater effluents containing various endocrine disrupting chemicals (EDCs) to coastal environments. Nonylphenols (NP) and bisphenol A (BPA) were found to be the most abundant EDCs in sewage effluents in Hong Kong. The environmental fate and ecological risk of these two EDCs remains largely unknown, particular for coastal systems with complex hydrodynamic flows. Based on a validated three-dimensional (3D) multiple-scale hydrodynamic model, a field-based study was conducted to track the two EDCs from potential sources to the only marine reserve in Hong Kong. The two compounds were detected in all seawater, suspended particle, and sediment samples, with higher aqueous concentrations in wet season than in dry season. High concentrations in sediments suggest sediment is a sink, posing an ecological risk to the benthos. The fate and transport of the two EDCs was predicted using a 3D near-field Lagrangian jet model seamlessly coupled with a 3D shallow water circulation model. The results suggested the NP and BPA in the marine reserve cannot be solely attributed to the nearby submarine sewage outfall, but likely concurrently contributed by other sources. This study calls for more effective measures of reducing the use and release of these EDCs, and research to investigate their impacts on the marine benthos. Graphical abstract: Image 1 Highlights: Environmental fate of NP and BPA was investigated from sources to a marine reserve. Higher aqueous concentrations were detected in bottom water during wet season. High sedimental concentrations associated with TOC pose ecological risk. 3D hydrodynamic model suggests additional sources than submarine outfall discharge. Abstract : Field-based studies integrated with validated 3D hydrodynamic models reveal the environmental fate and risk of two endocrine disruptors from multiple sources to the only marine reserve in Hong Kong.